A multimodal mixed methods approach for examining recontextualisation patterns of violent extremist images in online media. (March 2018) - Tan, Sabine; O'Halloran, Kay L.; Wignell, Peter; Chai, Kevin; Lange, Rebecca
Abstract: This paper uses a multimodal mixed methods approach for exploring general recontextualisation patterns of violent extremist images in online media. Specifically, the paper reports on the preliminary findings of a preliminary study which investigates various patterns in the reuse of images which appear in ISIS's official propaganda magazines Dabiq and Rumiyah by others across various public online media platforms (e.g. news websites, social media news aggregates, blogs). Using a mixed methods approach informed by multimodal discourse analysis, and combined with data mining and information visualisation, the study addresses questions such as which types of images produced and used by ISIS in its propaganda magazines recirculate most frequently in other online media over time, on which types of online media these images reappear, and in which contexts they are used and reused on these websites, that is that is, whether the tone of the message is corporate (formal) or personal (informal). Preliminary findings from the study suggest different recontextualisation patterns for certain types of ISIS-related images of over time. The study also found that the majority of violent extremist images used in the sample analysis appear to circulate most frequently on Western news and politics websites and news aggregate platforms, in predominantly formal contexts.